Optimalisasi Budidaya Madu sebagai Alternatif Peningkatan Ekonomi Masyarakat di Desa Sukandebi Kabupaten Karo - Muzkiati Muzkiati; M. Fikri Tanjung; Rushel Hardi; Abdul Haris Veriyadna; Ira Suryani (BADAN PENERBIT STIEPARI PRESS, 2025)
Suka Ndebi Village, Naman Teran District, Karo Regency, is a village located in the highlands at the foot of Mount Sinabung. Although 88% of its residents work as farmers, not all residents own their own agricultural land. It was recorded that 25% of the residents do not own their own land and work as salaried farmers, so the community’s economic level is classified as lower-middle class. Through the Community Service Program (KKN), the team discovered another untapped economic potential: honey bee cultivation. One villager has successfully cultivated honey independently and shown quite promising results. This Prompted the KKN team to conduct observations and analysis regarding the potential for developing honey cultivation as an alternative or additional source of income for the village community. This study aims to explore the extent to which honey cultivation can be a sustainable economic solution amidst limited agricultural land ownership. The methods used included field observations, interviews with residents and village officials, and literature review related to honey cultivation.